Computer-assisted sperm analysis of the epididymal spermatozoa in dromedary camels suffering from penile and preputial pathological problems - Ali, Montaser Elsayed; Gao, Min; Essawi, Walaa M.; Osman, Ahmed Yassen M.; Hussein, Mohamed K.; Abdelrahman, Mohamed; Al-Saeed, Fatimah A.; Hussein, Hassan A.; Liu, Yong-bin; Mohamed, Ragab Hassan (Frontiers in Veterinary Science, 2025)
Dromedary camels are the most vulnerable animals to penile and preputial pathology due to the aggressive nature of mating and injuries during transit, which could impair the semen quality. Hence, this study was performed to monitor the penile and preputial pathological conditions in male dromedary camels, as well as their impact on epididymal spermatozoa, by utilizing computer-assisted sperm analysis (CASA) and correlation analysis with testosterone concentrations. A total of 60 male dromedary camels were examined for penile and preputial pathological problems. The camels were grouped based on the absence or presence of the pathology conditions: (i) camels with normal penis and prepuce, (ii) camels with balanoposthitis, (iii) camels with penile trauma, (iv) camels with prolapsed prepuce, (v) camels with phimosis, and (vi) camels with penile tumors. The results revealed that there were significant increases in sperm concentration (Conc., M/ml), curvilinear velocity (VCL, μm/s), eat-cross frequency (BCF, Hz), and straightness (STR, VSL/VAP) of the epididymal tail semen in camels with prolapsed prepuce. There were increases in progressive motility (PR), VCL, straight line velocity (VSL, μm/s), average path velocity (VAP, μm/s), BCF, and STR in the sperms of the group with phimosis, but the differences were non-statistically significant. Furthermore, the CASA parameters of the epididymal tail semen in the group with penile tumor showed an increase in PR (%), VCL, VSL, VAP, BCF, and STR (%) compared to those in the group with normal penis and prepuce. However, the CASA parameters of the epididymal body in the group with penile tumor showed a significant increase in vitality, total motility (TM), non-progressive motility (NP), mean angular degree (MAD), linearity (LIN, VSL/VCL), VSL, amplitude of lateral head displacement (ALH, μm), VAP, BCF, and STR compared to those in the group with normal penis and prepuce. There were no discernible differences in testosterone concentrations among the groups. There was a negative correlation (p < 0.05, r = 0.411–0.459) between testosterone concentration and CASA parameters of the epididymal tail semen in camels with penile and preputial pathological conditions. In comparison, there were no discernible differences in correlation (p > 0.5, r = 0.074–0.360) between testosterone concentration and CASA parameters of the epididymal body and head semen in camels with penile and preputial pathology. In conclusion, the semen quality of male dromedary camels could be affected by the penile and preputial pathological problems, while the testosterone concentration was not affected.